Meloxicam Targets COX-2/NOX1/NOX4/Nrf2 Axis to Ameliorate the Depression-like Neuropathology Induced by Chronic Restraint Stress in Rats - Hany H. Arab; Ali Khames; Mostafa K. Mohammad; Shuruq E. Alsufyani; Ahmed M. Ashour; Azza A. K. El-Sheikh; Hany W. Darwish; Amany M. Gad (MDPI AG, 2023)
Meloxicam has shown significant neuroprotection in experimental models of stroke, Alzheimer's disease, and Parkinson's disease. However, the potential of meloxicam to treat depression-like neuropathology in a chronic restraint stress (CRS) model and the associated molecular changes has been insufficiently explored. The current work aimed to explore the potential neuroprotective actions of meloxicam against CRS-evoked depression in rats. In the current experiments, animals received meloxicam (10 mg/kg/day; i.p.) for 21 days, and CRS was instigated by restraining the animals for 6 h/day during the same period. The sucrose preference test and the forced swimming test were used to explore the depression-linked anhedonia/despair, whereas the open-field test examined the animals' locomotor activity. The current findings revealed that CRS elicited typical depression behavioral anomalies in the animals, including anhedonia, despair, and diminished locomotor activity; these findings were reinforced with Z-normalization scores. These observations were corroborated by brain histopathological changes and increased damage scores. In CRS-exposed animals, serum corticosterone spiked, and the hippocampi revealed decreased monoamine neurotransmitter levels (norepinephrine, serotonin, and dopamine). Mechanistically, neuroinflammation was evident in stressed animals, as shown by elevated hippocampal TNF-α and IL-1β cytokines. Moreover, the hippocampal COX-2/PGE2 axis was activated in the rats, confirming the escalation of neuroinflammatory events. In tandem, the pro-oxidant milieu was augmented, as seen by increased hippocampal 8-hydroxy-2'-deoxyguanosine alongside increased protein expression of the pro-oxidants NOX1 and NOX4 in the hippocampi of stressed animals. In addition, the antioxidant/cytoprotective Nrf2/HO-1 cascade was dampened, as evidenced by the lowered hippocampal protein expression of Nrf2 and HO-1 signals. Interestingly, meloxicam administration mitigated depression manifestations and brain histopathological anomalies in the rats. These beneficial effects were elicited by meloxicam's ability to counteract the corticosterone spike and hippocampal neurotransmitter decrease while also inhibiting COX-2/NOX1/NOX4 axis and stimulating Nrf2/HO-1 antioxidant pathway. Together, the present findings prove the neuroprotective/antidepressant actions of meloxicam in CRS-induced depression by ameliorating hippocampal neuroinflammation and pro-oxidant changes, likely by modulating COX-2/NOX1/NOX4/Nrf2 axis.